AM-FM texture image analysis in multiple sclerosis brain white matter lesions - Loizou, Christos P.; Murray, Víctor; Pattichis, Marios S.; Pantziaris, Marios; Seimenis, Ioannis; Pattichis, Constantinos S. (My University, 2010)
In this study we investigate the use of multiscale Amplitude Modulation-Frequency Modulation (AM-FM) methods for analyzing brain white matter lesions that are associated with multiple sclerosis MRI lesions imaged at 0 and 6-12 months. We use the instantaneous amplitude (IA) and the instantaneous frequency (IF) to assess disease progression. The IA and the IF were calculated in transverse sections of T2- weighted magnetic resonance (MR) images acquired from 38 symptomatic untreated subjects between the first and the second examination scan. The findings suggest that the high-, medium-, and low- frequency scale instantaneous amplitude and frequency can be used to differentiate between normal tissue and lesions at 0 and 6-12 months. Moreover, support vector machine (SVM) models gave satisfactory results for differentiating lesions at 0 months using the medium scale IA and IF components for expanded disability status scale (EDSS) <=2 and EDSS >2. Further work is needed with more subjects in validating the proposed AM-FM analysis. © 2010 International Federation for Medical and Biological Engineering.
Keywords: Multiple sclerosis; AM-FM analysis; Brain white matter; Disease progression